TEACHING LISTENING COMPREHENSION OF DESCRIPTIVE TEXT BASED ON 2013 CURRICULUM AT 10TH GRADE OF SENIOR HIGH SCHOOL - Dianita Putri Pratama; Johannes Jefria Gultom (Universitas Negeri Medan, 2018)
This study was aimed at describing how the teachers taught listening comprehension of descriptive text based on 2013 Curriculum and describing the reasons of why the teachers did the ways. This study was conducted by using descriptive qualitative research design. The data sources of the research were the English teachers of SMA Immanuel Medan. The data were the processes of teaching listening comprehension of descriptive text and the reasons of why the teachers did the ways of teaching. The techniques of collecting data were observation and interview. The data were analyzed by using interactive model which were data condensation, data display, and conclusion drawing. The results showed that the teachers used scientific approach steps in learning activities based on 2013 Curriculum in the teaching listening comprehension of descriptive text and the underlying reasons of the teachers‟ ways in teaching listening comrehension were the teachers believed that the students the students could comprehend and understandthe text by comparing the kind of texts, knowing the definition and text strucutre of texts, translating the difficult words and repeating the the recording of material. The knowledge of mastery the concept of teaching listening comprehension and skill of realization of the concept into real teaching behaviors will help the students‟ skill of listening comprehension be better.